COVID-19-Related Stressors and Mental Health Among Chinese College Students: A Moderated Mediation Model - Han, Zaichao; Tang, Xiujuan; Li, Xiaoshan; Shen, Youtian; Li, Li; Wang, Jingjing; Chen, Xiaowei; Hu, Zhijun (Frontiers in Public Health, 2021)
This study aimed to examine the relation between COVID-19-related stressors and mental health among Chinese college students during epidemic outbreaks. Five hundred and fifty Chinese college students were invited to complete an anonymous survey, and the data were analysed with SPSS 16.0 software. The results showed that the number of stressors had both negative direct and indirect (through risk perception of being infected with COVID-19 disease) impacts on college students’ mental health. Both adaptive coping and online learning satisfaction positively predicted mental health, and adaptive coping could be regarded as a buffer that attenuates the negative effect of the COVID-19-related stressors on risk perception of being infected with COVID-19 disease, and the negative impacts of risk perception of being infected with COVID-19 disease on mental health. Regarding demographic variables, females and students in higher grades tend to have a higher perceived risk of COVID-19 infection and poorer mental health during epidemics. These findings enrich our understanding of the impact of the COVID-19 pandemic on adults and have implications for university counselling services during times of acute, large-scale infective disease outbreaks.